TANTANGAN PENGEMBANGAN RUMAH DATA KEPENDUDUKAN DI KABUPATEN SIDOARJO - Kustanto, Munari (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2020)
ABSTRACT Population data plays an important role to succeed in the development regencies, including in Sidoarjo Regency. The valid and accountable population data is an absolute requirement that development policies are right on target, ranging from providing assistance to setting targets and development programs. Using a descriptive qualitative approach, this study aims to evaluate the condition of the Population Data House (Rumah Dataku) in Sidoarjo Regency as well as to identify the challenges of its development, both internal and external. The results showed that of the 353 villages in the Sidoarjo regency, there were only 42 villages / kelurahan (11.90%) having a KB (Family Planning) village. Of this number, not all of them had a Dataku House. There were only three KB villages (7%) that had Dataku Houses. Viewed from the aspect of availability, presentation and updating of existing data, the KB Villages and Dataku Houses in Sidoarjo Regency have not shown good performance. The internal and external challenges faced in developing Dataku Houses in Sidoarjo Regency included the budget constraints, limited resources (human resources and supporting infrastructure), lack of coordination, and lack of community understanding and participation. The Sidoarjo Regency Government may overcome these challenges through organizing a KB Village competition and a Thematic Community Service Program, making an application for the Dataku House, increasing the role of the KB Village Working Group, and training for KB management and extension workers. Keywords: KB village, development, Rumah Dataku